Battery and method for formation and aging thereof

CN122800757APending Publication Date: 2026-09-22EVE POWER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611113915.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-24
Publication Date
2026-09-22

AI Technical Summary

Technical Problem

[0005]本发明的主要目的在于提供一种电池及其化成老化方法,以解决相关技术中的磷酸锰铁锂电芯在化成与老化工艺中因电解液浸润不充分、SEI膜结构疏松以及锰离子溶出与气体残留,导致制程内未完成的副反应在高温应用阶段持续加剧的问题

Benefits of technology

[0016]应用本申请的技术方案,本申请大幅提升首次注液的比例,能够确保电解液在电芯组装初期就充分浸润磷酸锰铁锂(LMFP)正极颗粒的间隙与负极的孔隙,从而为后续化成阶段的SEI膜的形成,电解液初步分解提供充足的原料,避免因前期电解液不足导致的反应不彻底,进而从源头减少后续电解液与正负极产生副反应。依托一次注液提供的充足电解液,本申请进一步控制化成的最高SOC在上述范围能够使负极形成50~80nm、致密度>90%的SEI膜,是SEI膜的抗高温破损率提升60%以上。LMFP正极中Mn2+/Fe2+的氧化率超95%(传统方法为80%);同时控制化成的最高SOC≤90%,能够避免Mn3+过度溶出。随后,将老化阶段的时间(a)、温度(b)与SOC(c)三者以K=cb/a关系进行协同调控,而老化均衡系数K的取值范围对电芯高温稳定性具有决定性影响:K值与LMFP电芯特性实现了完美匹配,既能够确保老化阶段充分消耗残留电解液、释放前期产气,又能够有效抑制Mn3+过度溶出与SEI膜破损,从而实现低产气、低衰减以及高稳定。当K值低于0.056时,老化反应强度不足,残留电解液与未释放气体在后续高温环境中持续引发副反应,导致电池的厚度和产气量提升;当K值高于2.5时,老化反应过度,引发Mn3+溶出量激增与SEI膜破损,电池的厚度和产气量大幅提升,电池的容量保持率下降,从而完全无法满足高温应用场景的使用需求。因此,本申请控制K的取值范围在上述范围,能够明显提高电池高温性能的稳定性。最后,在分容阶段施加上述范围内的拘束力,能够排出芯包内的气体,从而改善电芯厚度和界面。综上,本申请通过注液比例、化成SOC、老化以及分容等协同优化,能够改善电芯在循环和存储过程中的因产气导致的厚度变化,优化界面和阻抗,从而提高电芯的性能,尤其是高温场景下的可靠性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application provides a battery and a formation and aging method thereof. The formation and aging method comprises the following steps: sequentially performing one-time liquid injection, standing, formation, secondary liquid injection, aging and capacity grading on an electric core to obtain the battery; the liquid injection amount of the one-time liquid injection accounts for 85-97% of the total liquid injection amount; the highest SOC of the formation is 75-90%; the aging time is defined as a, the unit being h; the aging temperature is defined as b, the unit being DEG C; the SOC of the aging is defined as c; the numerical values of a, b and c satisfy the formula: K=(c*b) / a, K is an aging balance coefficient, 0.056<=K<=2.5; the restraint force of the capacity grading is greater than or equal to 5000N. The formation and aging method solves the problem that the uncompleted side reaction in the process continuously intensifies in the high-temperature application stage due to the insufficient impregnation of electrolyte, the loose SEI film structure and the manganese ion dissolution and gas residue of the lithium manganese iron phosphate electric core in the formation and aging process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and more specifically, to a battery and its formation and aging method. Background Technology

[0002] While lithium manganese iron phosphate (LMFP) cells offer advantages such as high energy density and high safety, current manufacturing processes are not specifically tailored to their material properties (Mn). 3+ (The ease of leaching and the special requirements of the SEI membrane) lead to problems such as gas generation and side reactions under high-temperature conditions.

[0003] Currently, the manufacturing process of LMFP cells generally fails to resolve the core contradiction between "reaction sufficiency" and "gas removal": 1) Insufficient initial electrolyte injection or an imbalance in the ratio of secondary electrolyte injection during the initial injection stage results in insufficient initial electrolyte wetting, leading to inadequate coverage of the gaps between LMFP positive electrode particles and failure to participate in the process reaction, resulting in excessive residue in the later stages. 2) The formation stage uses low SOC (40~60%) to control gas production, resulting in incomplete growth and a loose structure of the SEI film on the negative electrode, making it difficult to withstand subsequent high-temperature shocks. 3) The aging process only uses mild conditions of 25~50℃ for 6~8 hours, failing to accelerate the growth of Mn. 3+ There were no potential side reactions related to dissolution, nor were any trace amounts of gas generated during the process released. 4) There was no effective restraint force during volume separation, causing residual gas to remain in the core package voids.

[0004] The combined effects of these process defects result in three major risks remaining after the battery cell is produced: "unstable SEI film," "residual electrolyte," and "trapped gas." These risks make the porous SEI film prone to damage under subsequent high-temperature environments, leading to the release of dissolved Mn. 3+ Side reactions can occur with residual electrolyte, and the trapped gas expands upon heating, further exacerbating Mn dissolution and SEI damage, creating a vicious cycle. Ultimately, this leads to a cell thickness increase exceeding 5%, capacity decay exceeding 8%, and internal resistance increase exceeding 15%, severely impacting the reliability of LMFP batteries in high-temperature environments. Therefore, there is an urgent need to develop a high-stability formation and aging process for lithium manganese iron phosphate (LMFP) cells. Summary of the Invention

[0005] The main objective of this invention is to provide a battery and its formation and aging method to solve the problem in related technologies where insufficient electrolyte wetting, loose SEI film structure, manganese ion dissolution, and gas residue in the formation and aging process of lithium iron phosphate cells lead to the continuous aggravation of unfinished side reactions during the high-temperature application stage.

[0006] To achieve the above objectives, according to one aspect of the present invention, a battery formation and aging method is provided, comprising: sequentially performing a first electrolyte injection, settling, formation, a second electrolyte injection, aging, and capacity testing on a battery cell to obtain a battery; wherein the amount of electrolyte injected in the first electrolyte injection accounts for 85-97% of the total electrolyte volume; the highest SOC of formation is 75-90%; the aging time is defined as a in hours; the aging temperature is defined as b in degrees Celsius; the SOC of aging is defined as c; the values ​​of a, b, and c satisfy the formula: K = (c × b) / a, where K is the aging equilibrium coefficient, 0.056 ≤ K ≤ 2.5; and the constraint force of capacity testing is ≥ 5000 N.

[0007] Furthermore, the aging time is 12~120h, the aging temperature is 45~60℃, and the SOC of aging is 15~50%.

[0008] Furthermore, the formation process includes: charging the stationary battery cell at 0.05~0.1C to 10~15% SOC, then charging it at 0.1~0.2C to 25~35% SOC, continuing to charge it at 0.2~0.5C to 75~90% SOC, and finally discharging it to 15~50% SOC.

[0009] Furthermore, the restraining force of the capacity is 5000~15000N.

[0010] Furthermore, the battery cell includes a positive electrode, which includes a positive electrode material, and the positive electrode material includes lithium manganese iron phosphate material.

[0011] Furthermore, the settling temperature is 45~55℃, and the settling time is 36~120h.

[0012] Furthermore, the volume of secondary injection accounts for 3-15% of the total injection volume.

[0013] Furthermore, the electrolyte filling coefficient of the battery cell is 3.0~3.3g / Ah.

[0014] Furthermore, the battery cell is a square aluminum-cased battery cell and / or a pouch battery cell; the moisture content in the battery cell is <200ppm by mass.

[0015] According to another aspect of the present invention, a battery is provided, which is a battery obtained by the above-described formation and aging method.

[0016] By applying the technical solution of this application, the proportion of initial electrolyte injection is significantly increased. This ensures that the electrolyte fully wets the gaps between the lithium manganese iron phosphate (LMFP) cathode particles and the pores of the anode during the initial stage of cell assembly. This provides sufficient raw materials for the formation of the SEI film and the initial decomposition of the electrolyte in the subsequent formation stage, avoiding incomplete reactions due to insufficient electrolyte in the early stages. This reduces side reactions between the electrolyte and the cathode and anode from the source. Relying on the sufficient electrolyte provided by the initial injection, this application further controls the maximum SOC of formation within the aforementioned range, enabling the formation of a 50-80 nm SEI film with a density >90% on the anode, improving the high-temperature damage resistance of the SEI film by more than 60%. (LMFP cathode Mn) 2+ / Fe 2+ The oxidation rate exceeds 95% (compared to 80% by traditional methods); simultaneously, the maximum SOC of formation is controlled to ≤90%, which can avoid Mn oxidation. 3+ Excessive dissolution. Subsequently, the aging stage time (a), temperature (b), and SOC (c) were synergistically controlled using the relationship K=cb / a. The range of values ​​for the aging equilibrium coefficient K has a decisive impact on the high-temperature stability of the cell: the K value is perfectly matched with the characteristics of the LMFP cell, ensuring that the residual electrolyte is fully consumed and the gas generated in the early stage is released during the aging stage, while effectively suppressing Mn. 3+ Excessive dissolution and SEI film damage result in low gas production, low degradation, and high stability. When the K value is below 0.056, the aging reaction intensity is insufficient, and residual electrolyte and unreleased gas continue to trigger side reactions in the subsequent high-temperature environment, leading to increased battery thickness and gas production. When the K value is above 2.5, the aging reaction is excessive, triggering Mn... 3+ The surge in dissolution and SEI film damage significantly increases battery thickness and gas production, leading to a decrease in capacity retention and making the battery completely unsuitable for high-temperature applications. Therefore, this application controls the value of K within the aforementioned range, which significantly improves the stability of the battery's high-temperature performance. Finally, applying a restraining force within the aforementioned range during the capacity testing stage can expel gas from the cell pack, thereby improving cell thickness and interface. In summary, this application, through synergistic optimization of electrolyte injection ratio, formation SOC, aging, and capacity testing, can improve cell thickness changes caused by gas production during cycling and storage, optimize interface and impedance, and thus improve cell performance, especially reliability in high-temperature scenarios. Detailed Implementation

[0017] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present invention will now be described in detail with reference to the embodiments.

[0018] As analyzed in the background section of this application, the prior art has the problem that in the formation and aging process of lithium manganese iron phosphate cells, due to insufficient electrolyte wetting, loose SEI film structure, and manganese ion dissolution and gas residue, the unfinished side reactions in the process continue to intensify during the high-temperature application stage. In order to solve the above problems, this application provides a battery and its formation and aging method.

[0019] In a typical embodiment of this application, a battery formation and aging method is provided, which includes: sequentially performing a first electrolyte injection, standing, formation, a second electrolyte injection, aging, and capacity testing on a battery cell to obtain a battery; wherein, the amount of electrolyte injected in the first electrolyte injection accounts for 85-97% of the total electrolyte volume; the highest SOC of formation is 75-90%; the aging time is defined as a, in hours; the aging temperature is defined as b, in degrees Celsius; the SOC of aging is defined as c; the values ​​of a, b, and c satisfy the formula: K = (c × b) / a, where K is the aging equilibrium coefficient, 0.056 ≤ K ≤ 2.5; and the constraint force of capacity testing is ≥ 5000 N.

[0020] This application significantly increases the initial electrolyte injection ratio, ensuring that the electrolyte fully wets the gaps between the lithium manganese iron phosphate (LMFP) cathode particles and the pores of the anode during the initial cell assembly stage. This provides sufficient raw materials for the formation of the SEI film and the initial decomposition of the electrolyte in the subsequent formation stage, avoiding incomplete reactions due to insufficient electrolyte in the early stages, and thus reducing side reactions between the electrolyte and the cathode and anode from the source. Relying on the sufficient electrolyte provided by the initial injection, this application further controls the maximum SOC of formation within the aforementioned range, enabling the formation of a 50-80 nm SEI film with a density >90% on the anode, improving the high-temperature damage resistance of the SEI film by more than 60%. (LMFP cathode Mn) 2+ / Fe 2+ The oxidation rate exceeds 95% (compared to 80% by traditional methods); simultaneously, the maximum SOC of formation is controlled to ≤90%, which can avoid Mn oxidation. 3+ Excessive dissolution. Subsequently, the aging stage time (a), temperature (b), and SOC (c) were synergistically controlled using the relationship K=cb / a. The range of values ​​for the aging equilibrium coefficient K has a decisive impact on the high-temperature stability of the cell: the K value is perfectly matched with the characteristics of the LMFP cell, ensuring that the residual electrolyte is fully consumed and the gas generated in the early stage is released during the aging stage, while effectively suppressing Mn. 3+ Excessive dissolution and SEI film damage result in low gas production, low degradation, and high stability. When the K value is below 0.056, the aging reaction intensity is insufficient, and residual electrolyte and unreleased gas continue to trigger side reactions in the subsequent high-temperature environment, leading to increased battery thickness and gas production. When the K value is above 2.5, the aging reaction is excessive, triggering Mn... 3+The surge in dissolution and SEI film damage significantly increases battery thickness and gas production, leading to a decrease in capacity retention and making the battery completely unsuitable for high-temperature applications. Therefore, this application controls the value of K within the aforementioned range, which significantly improves the stability of the battery's high-temperature performance. Finally, applying a restraining force within the aforementioned range during the capacity testing stage can expel gas from the cell pack, thereby improving cell thickness and interface. In summary, this application, through synergistic optimization of electrolyte injection ratio, formation SOC, aging, and capacity testing, can improve cell thickness changes caused by gas production during cycling and storage, optimize interface and impedance, and thus improve cell performance, especially reliability in high-temperature scenarios.

[0021] Furthermore, the volume of fluid injected in a single injection can account for 85%, 87%, 90%, 92%, 95%, or 97% of the total volume injected. The value of K can be 0.056, 0.08, 0.1, 0.3, 0.5, 0.7, 1.0, 1.2, 1.5, 1.7, 2.0, 2.2, or 2.5.

[0022] In one embodiment of this application, the aging time is 12~120h, the aging temperature is 45~60℃, and the SOC of aging is 15~50%.

[0023] Optimizing the aging time, temperature, and SOC within the above ranges, and satisfying the formula K=cb / a and the range of K values, not only helps to fully consume the residual electrolyte and release the gas generated in the early stage, but also helps to reduce Mn. 3+ Excessive dissolution and SEI film damage enable synergistic optimization of low gas production, low expansion, and high capacity retention in lithium manganese iron phosphate cells under high-temperature environments, thereby further improving their cycle stability and safety.

[0024] Furthermore, the aging time can be 12h, 24h, 36h, 48h, 60h, 72h, 84h, 96h, 108h, 120h, etc. The aging temperature can be 45℃, 47℃, 50℃, 55℃, 57℃, 60℃, etc. The SOC (c) of aging can be 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, etc. The SOC of aging is c, meaning the value of c is 0.15~0.5.

[0025] In one embodiment of this application, the formation process includes: charging the cell after it has been left to stand at 0.05~0.1C to 10~15% SOC, then charging it at 0.1~0.2C to 25~35% SOC, continuing to charge it at 0.2~0.5C to 75~90% SOC, and finally discharging it to 15~50% SOC.

[0026] By employing a segmented, stepped charging path during the formation stage, the cell is first charged with a low current of 0.05–0.1C to 10–15% SOC after resting. This helps the initial SEI film to slowly form on the negative electrode surface at a low current density, reducing localized interface inhomogeneity or accelerated electrolyte decomposition caused by excessively rapid lithium-ion insertion. Then, it is charged with a medium current of 0.1–0.2C to 25–35% SOC, which helps promote the uniform extension and densification of the SEI film. Finally, it is charged with a higher current of 0.2–0.5C to 75–90% SOC, which helps complete most of the lithium-ion insertion while maintaining a certain stability in the SEI film. This reduces the risk of incomplete SEI film growth and porous structure due to excessively low SOC, and the risk of Mn content problems due to excessively high SOC. 3+ Excessive dissolution. The final discharge reaches 15-50% SOC to release trace amounts of gas accumulated during formation and stabilize the electrode structure. This formation process, combined with a high single-fill volume providing a sufficient electrolyte environment, helps further improve the uniformity, density, and thermal stability of the SEI film, thereby fundamentally mitigating the performance degradation and expansion risks caused by interfacial instability during high-temperature aging of lithium manganese iron phosphate cells.

[0027] In one embodiment of this application, the restraining force of the gradation is 5000~15000N.

[0028] The optimal constraint force applied to the cell during the capacity testing stage is within the aforementioned range. This helps maintain the cell's structural stability during the process, promotes the full escape of residual gas, and reduces the risk of structural degradation caused by excessive constraint force, such as cell-pack interface damage, separator deformation, or localized lithium dendrite concentration. This further enhances the cell's cycle stability and safety performance under high-temperature conditions while maintaining cell thickness consistency and interface integrity after formation and aging. Furthermore, the constraint force during capacity testing can be 5000N, 7000N, 9000N, 10000N, 12000N, or 15000N.

[0029] In one embodiment of this application, the battery cell includes a positive electrode, the positive electrode includes a positive electrode material, and the positive electrode material includes lithium manganese iron phosphate material.

[0030] The formation and aging method of this application is more suitable for battery cells using lithium manganese iron phosphate as the cathode material, and it specifically optimizes its unique Mn content. 3+ Addressing dissolution issues and the need for an SEI film, thereby further improving the structural stability and cycle reliability of the battery cell under high-temperature environments. Lithium manganese iron phosphate material can be used for LiMn... 0.5 Fe 0.5 PO4 or LiMn 0.4 Fe 0.6 PO4, etc.

[0031] In one embodiment of this application, the settling temperature is 45~55℃ and the settling time is 36~120h.

[0032] Controlling the temperature and time of the initial electrolyte injection within the aforementioned range helps the electrolyte to fully penetrate the microporous structure between the positive and negative electrode active material particles under gentle and continuous thermal drive. This improves the uniformity and sufficiency of wetting, reducing the risk of localized reactive differences due to insufficient wetting or solvent decomposition caused by over-wetting. The synergistic effect of these wetting conditions and the high initial electrolyte injection volume promotes uniform SEI film formation in subsequent formation stages, reducing localized side reactions and abnormal gas evolution caused by uneven electrolyte distribution. This enhances the structural stability and cycle reliability of the battery cell under high-temperature conditions. Furthermore, the wetting temperature can be 45℃, 47℃, 50℃, 52℃, 55℃, etc., and the wetting time can be 36h, 48h, 60h, 72h, 84h, 96h, 108h, 120h, etc.

[0033] In one embodiment of this application, the amount of fluid injected in the second injection accounts for 3-15% of the total amount of fluid injected.

[0034] The total electrolyte injection volume is the sum of the volume injected during the primary injection and the volume injected during the secondary injection. Controlling the secondary electrolyte injection volume within the aforementioned range helps reduce cell gas generation at the source. Performing the secondary electrolyte injection during the window period after formation is complete, the main gases have been released, but aging has not yet begun helps ensure the total electrolyte volume meets the aging reaction requirements and reduces secondary side reactions caused by excess electrolyte. Furthermore, the secondary electrolyte injection volume can account for 3%, 5%, 7%, 10%, 12%, 15% of the total electrolyte injection volume, etc.

[0035] In one embodiment of this application, the electrolyte filling coefficient of the battery cell is 3.0~3.3g / Ah.

[0036] Controlling the electrolyte filling coefficient within the aforementioned range helps regulate the amount of electrolyte added, establishing a stable relationship between it and the cell capacity. This ensures that, under conditions of high electrolyte filling ratio and high SOC formation, the electrolyte fully wets the positive and negative electrode pore structures, reducing unevenness or localized drying of the SEI film due to insufficient wetting. Simultaneously, it reduces the risk of excessive electrolyte causing exacerbated side reactions and uncontrolled gas evolution during the aging stage. Furthermore, the electrolyte filling coefficient can be 3.0 g / Ah, 3.1 g / Ah, 3.2 g / Ah, 3.3 g / Ah, etc.

[0037] In one embodiment of this application, the battery cell is a square aluminum-cased battery cell and / or a pouch battery cell; the moisture content in the battery cell is <200ppm.

[0038] All of the above-mentioned types of battery cells are suitable for the formation and aging method of this application. Controlling the moisture content in the battery cell within the above-mentioned range helps to reduce side reactions caused by moisture during the formation and aging process, and reduces the formation of hydrogen fluoride and Mn. 3+ Dissolution, loose SEI film and abnormal gas precipitation.

[0039] In another typical embodiment of this application, a battery is provided, which is a battery obtained by the above-described formation and aging method.

[0040] Batteries produced by the above-mentioned formation and aging methods have good high-temperature stability and can meet industrial needs, such as energy storage power stations and commercial vehicles, which need to withstand environments above 50°C for a long time.

[0041] The beneficial effects of this application will be further illustrated below with reference to the embodiments.

[0042] Example 1

[0043] We provide pre-assembled, square-shelled battery cells with a moisture content of <200ppm. The positive electrode material in the cells is lithium manganese iron phosphate (LiMn). 0.4 Fe 0.6 PO4) is injected once, with an injection coefficient of 3.2g / Ah. The amount of liquid injected in one injection accounts for 93% of the total amount of liquid injected. Specifically, for a 50Ah cell, the liquid retention is 160g, and the amount of liquid injected in one injection is 148.8g.

[0044] After one electrolyte injection, the battery cell was placed in an oven at 45°C for 36 hours, and then formed. The formation process was as follows: the cell was charged at 0.05C to 10% SOC, then charged at 0.1C to 30%, then charged at 0.33C to 85% SOC (maximum formation SOC), and then discharged to 30% SOC.

[0045] After formation, a second electrolyte injection is performed, with the amount of electrolyte injected accounting for 7% of the total amount injected, i.e., replenishing the electrolyte to a retention volume of 160g. Then, aging is carried out under the following conditions: aging time (a) is 72h, aging temperature (b) is 45℃, aging SOC (c) is 30%, and the aging equilibrium coefficient K=(c×b) / a, K=0.1875, i.e., a, b and c satisfy the formula, and 0.056≤K≤2.5.

[0046] After aging is complete, capacity testing is performed with a constraint force of 10000N to obtain the battery.

[0047] Example 2

[0048] The difference from Example 1 is that the amount of liquid injected at one time accounts for 88% of the total amount of liquid injected; the standing temperature is 50°C and the time is 24h; the maximum formation SOC is 82%; the aging temperature (b) is 50°C, the aging time (a) is 48h, the aging SOC (c) is 25%, K is 0.2604, the capacity-separating restraint force is 7500N, and finally a battery is obtained.

[0049] Example 3

[0050] The difference from Example 1 is that the amount of liquid injected at one time accounts for 96% of the total amount of liquid injected; the standing temperature is 42°C and the time is 48h; the maximum formation SOC is 88%; the aging temperature (b) is 42°C, the aging time (a) is 96h, the aging SOC (c) is 35%, K is 0.1531, the capacity grading restraint force is 9500N, and finally a battery is obtained.

[0051] Example 4

[0052] The difference from Example 1 is that the liquid volume injected in the first injection accounts for 85% of the total liquid volume, and the liquid volume injected in the second injection accounts for 15% of the total liquid volume, thus finally obtaining the battery.

[0053] Example 5

[0054] The difference from Example 1 is that the formation process is as follows: set a current of 0.05C to charge to 10% SOC, switch to 0.1C to charge to 25%, then charge at 0.2C to 75% SOC, and then discharge to 50% SOC to finally obtain the battery.

[0055] Example 6

[0056] The difference from Example 1 is that the formation process is as follows: set a current of 0.1C to charge to 15% SOC, switch to 0.2C to charge to 35% SOC, then charge to 0.5C to 90% SOC, and then discharge to 15% SOC to finally obtain the battery.

[0057] Example 7

[0058] The difference from Example 1 is that the aging temperature (b) is 45°C, the aging time (a) is 120h, the SOC (c) of aging is 15%, and K is 0.056, and the battery is finally obtained.

[0059] Example 8

[0060] The difference from Example 1 is that the aging temperature (b) is 60°C, the aging time (a) is 12h, the SOC (c) of aging is 50%, K is 2.5, and the battery is finally obtained.

[0061] Example 9

[0062] The difference from Example 1 is that the capacity grading constraint force is 5000N, and the battery is finally obtained.

[0063] Example 10

[0064] The difference from Example 1 is that the capacity grading constraint force is 15000N, and the battery is finally obtained.

[0065] Comparative Example 1

[0066] The difference from Example 1 is that the aging temperature (b) is 43°C, the aging time (a) is 110h, the SOC (c) of aging is 13%, and K is 0.0508, and the battery is finally obtained.

[0067] Comparative Example 2

[0068] The difference from Example 1 is that the aging temperature (b) is 59°C, the aging time (a) is 11h, the SOC (c) of aging is 49%, and K is 2.63, resulting in a battery.

[0069] Comparative Example 3

[0070] The difference from Example 1 is that the aging temperature (b) is 45°C, the aging time (a) is 8 hours, the SOC (c) of aging is 50%, and K is 2.8125, and the battery is finally obtained.

[0071] Comparative Example 4

[0072] The difference from Example 1 is that the liquid volume injected in the first injection accounts for 80% of the total liquid volume, and the liquid volume injected in the second injection accounts for 20% of the total liquid volume, and finally a battery is obtained.

[0073] Comparative Example 5

[0074] The difference from Example 1 is that the highest SOC of the formation is 70%, and a battery is finally obtained.

[0075] Comparative Example 6

[0076] The difference from Example 1 is that the highest SOC of the formation is 95%, and a battery is finally obtained.

[0077] Comparative Example 7

[0078] The difference from Example 1 is that the capacity grading constraint force is 4000N, and the battery is finally obtained.

[0079] Test method:

[0080] Gas production: At 45℃ for 30 days, the gas produced by the battery cell was collected using an aluminum-plastic bag and the volume was tested.

[0081] Battery thickness increase: 300kfg of pressure-bearing thickness after 30 days at 45℃.

[0082] Capacity retention: Capacity retention after 500 cycles of SCCV / 1C at 25°C.

[0083] Internal resistance increase: The DCR growth rate after 500 cycles of SCCV / 1C at 25℃.

[0084] The test results are shown in Table 1.

[0085] Table 1

[0086]

[0087] As shown above, the performance comparison of LMFP cells under different aging equilibrium coefficient K values ​​reveals that the K value, as the core synergistic coefficient between series aging temperature, aging time, and aging SOC, has a decisive influence on the high-temperature stability of the cell. When the K value is in the range of 0.056~2.5, the cell exhibits significant performance advantages, fully demonstrating that this K value is perfectly matched with the characteristics of LMFP cells. It can ensure that the residual electrolyte is fully consumed and the gas generated in the early stage is released during the aging process, while effectively suppressing Mn. 3+ Excessive dissolution and SEI film damage achieve the goal of "low gas production, low degradation, and high stability." However, when the K value deviates from the above range (corresponding to ratios 1 to 3), the cell performance deteriorates sharply. When the K value is below 0.056, the aging reaction intensity is insufficient, and residual electrolyte and unreleased gas continue to trigger side reactions in the subsequent high-temperature environment, causing the battery thickness increase to rise to 5.5% and the gas production to rise to 6.2 mL. When the K value is above 2.5, the aging reaction is excessive, triggering Mn... 3+ The surge in dissolution and damage to the SEI film resulted in a battery thickness increase of up to 10.5%, gas production exceeding 8 mL, and capacity retention dropping below 94.2%, making it completely unsuitable for high-temperature applications.

[0088] In Comparative Example 4, the amount of electrolyte injected in a single injection was insufficient, resulting in inadequate wetting of the electrolyte in the early stage (failing to cover the gaps between the LMFP cathode particles) and excessive residue in the later stage.

[0089] In Comparative Example 5, the highest SOC of the formed material was low, resulting in incomplete growth of the negative electrode SEI film and a loose structure, making it difficult to withstand subsequent high-temperature shocks.

[0090] The highest SOC of formation in Comparative Example 6 was higher, resulting in Mn 3+ Excessive dissolution.

[0091] In Comparative Example 7, the confinement force of the volume division was too low, and it could not form an effective confinement force, resulting in residual gas remaining in the core cavity.

[0092] As can be seen from the above description, the embodiments of this application achieve the following technical effects:

[0093] This application significantly increases the initial electrolyte injection ratio, ensuring that the electrolyte fully wets the gaps between the lithium manganese iron phosphate (LMFP) cathode particles and the pores of the anode during the initial cell assembly stage. This provides sufficient raw materials for the formation of the SEI film and the initial decomposition of the electrolyte in the subsequent formation stage, avoiding incomplete reactions due to insufficient electrolyte in the early stages, and thus reducing side reactions between the electrolyte and the cathode and anode from the source. Relying on the sufficient electrolyte provided by the initial injection, this application further controls the maximum SOC of formation within the aforementioned range, enabling the formation of a 50-80 nm SEI film with a density >90% on the anode, improving the high-temperature damage resistance of the SEI film by more than 60%. (LMFP cathode Mn) 2+ / Fe 2+ The oxidation rate exceeds 95% (compared to 80% by traditional methods); simultaneously, the maximum SOC of formation is controlled to ≤90%, which can avoid Mn oxidation. 3+ Excessive dissolution. Subsequently, the aging stage time (a), temperature (b), and SOC (c) were synergistically controlled using the relationship K=cb / a. The range of values ​​for the aging equilibrium coefficient K has a decisive impact on the high-temperature stability of the cell: the K value is perfectly matched with the characteristics of the LMFP cell, ensuring that the residual electrolyte is fully consumed and the gas generated in the early stage is released during the aging stage, while effectively suppressing Mn. 3+ Excessive dissolution and SEI film damage result in low gas production, low degradation, and high stability. When the K value is below 0.056, the aging reaction intensity is insufficient, and residual electrolyte and unreleased gas continue to trigger side reactions in the subsequent high-temperature environment, leading to increased battery thickness and gas production. When the K value is above 2.5, the aging reaction is excessive, triggering Mn... 3+ The surge in dissolution and SEI film damage significantly increases battery thickness and gas production, leading to a decrease in capacity retention and making the battery completely unsuitable for high-temperature applications. Therefore, this application controls the value of K within the aforementioned range, which significantly improves the stability of the battery's high-temperature performance. Finally, applying a restraining force within the aforementioned range during the capacity testing stage can expel gas from the cell pack, thereby improving cell thickness and interface. In summary, this application, through synergistic optimization of electrolyte injection ratio, formation SOC, aging, and capacity testing, can improve cell thickness changes caused by gas production during cycling and storage, optimize interface and impedance, and thus improve cell performance, especially reliability in high-temperature scenarios.

[0094] The above are merely preferred embodiments of this application and are not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A method for the formation and aging of a battery, characterized in that, The formation aging method includes: The battery cell is subjected to a series of processes, including one electrolyte injection, settling, formation, a second electrolyte injection, aging, and capacity testing, to obtain the battery. In this case, the volume of fluid injected in a single injection accounts for 85-97% of the total volume of fluid injected. The highest SOC of the formation is 75-90%; The aging time is defined as a, in hours; the aging temperature is defined as b, in degrees Celsius; the SOC of aging is defined as c; the values ​​of a, b, and c satisfy the formula: K = (c × b) / a, where K is the aging equilibrium coefficient, 0.056 ≤ K ≤ 2.5; The binding force of the divided volume is ≥5000N.

2. The formation aging method according to claim 1, characterized in that, The aging time is 12~120h, the aging temperature is 45~60℃, and the SOC of the aging process is 15~50%.

3. The formation aging method according to claim 1, characterized in that, The formation process includes: charging the stationary battery cell at 0.05~0.1C to 10~15% SOC, then charging it at 0.1~0.2C to 25~35% SOC, continuing to charge it at 0.2~0.5C to 75~90% SOC, and finally discharging it to 15~50% SOC.

4. The formation aging method according to claim 1, characterized in that, The restraining force of the divided capacity is 5000~15000N.

5. The formation aging method according to any one of claims 1 to 4, characterized in that, The battery cell includes a positive electrode, the positive electrode includes a positive electrode material, and the positive electrode material includes lithium manganese iron phosphate material.

6. The formation aging method according to any one of claims 1 to 4, characterized in that, The settling temperature is 45~55℃, and the settling time is 36~120h.

7. The formation aging method according to any one of claims 1 to 4, characterized in that, The secondary injection volume accounts for 3-15% of the total injection volume.

8. The formation aging method according to any one of claims 1 to 4, characterized in that, The electrolyte injection coefficient of the battery cell is 3.0~3.3g / Ah.

9. The formation aging method according to any one of claims 1 to 4, characterized in that, The battery cell is a square aluminum-cased battery cell and / or a pouch battery cell; the moisture content of the battery cell is <200ppm by mass.

10. A battery, characterized in that, The battery is a battery obtained by the formation and aging method according to any one of claims 1 to 9.